Electronic credit record A comparative study - MUSTAFA AL NASRY (الرافدین للحقوق, 2019)
The availability and availability of information on the activity of merchants and companies contributes widely and certainly to the expansion and dissemination of diverse and varied commercial activities at the local, regional or international levels.The establishment of the existence of available information of a credit nature for all types of business activities has many advantages achieved by such information, which must be available and accessible to stakeholders from traders or others inside or outside the country, thus achieving a definite qualitative leap in the development of commercial and investment activity , By providing this accurate and correct information in accordance with the law.